Novel Approach to Track the Lifecycle of Inflammation from Chemokine Expression to Inflammatory Proteins in Sweat Using Electrochemical Biosensor - Jagannath, Badrinath; Pali, Madhavi; Lin, Kai‐Chun; Sankhala, Devangsingh; Naraghi, Pejman; Muthukumar, Sriram; Prasad, Shalini (Advanced materials technologies, 2022)
Inflammatory biomarkers are modulated during the course of any infectious disease, and currently, there is no wearable technology that enables patient management through noninvasive monitoring of these markers. This work is the first demonstration of the discovery and quantification of interferon‐inducible protein (IP‐10) and tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL), two key prognostic markers of infection in human sweat. The levels of IP‐10 and TRAIL in sweat are quantified, validated, and confirmed using a standard reference method through preclinical human subject studies. Additionally, simultaneous and continuous detection of IP‐10, TRAIL, and C‐reactive protein (CRP), for infection monitoring in sweat using a wearable SWEATSENSER device is demonstrated. The SWEATSENSER is ultrasensitive with a limit of detection of 1 pg mL−1 (IP‐10 and TRAIL), 0.2 ng mL−1 (CRP) with a wide dynamic range. Bland–Altman analysis demonstrates good agreement between SWEATSENSER and standard reference methods through human subject studies. Serum to sweat relationship demonstrates the potential of the SWEATSENSER to track infection etiology. Wearable sensor for real‐time monitoring of infection markers in sweat to provide active feedback on health status.